Ответы и объяснения

2014-01-26T09:51:00+00:00
2cosx+cos2x=2sinx2cosx+(2cos^2x-1)-2sinx=02cosx+2cos^2x-(sin^2x+cos^2x)-2sinx=02cosx+2cos^2x-sin^2x-cos^2x-2sinx=0
cos^2x+2cosx-sin^2x-2sinx=0
Произведём группировкуcos^2x-sin^2x+2cosx-2sinx=0(cosx+sinx)(cosx-sinx)+2(cosx-sinx)=0выносим общий множ. за скобки(cosx-sinx)(cosx+sinx+2)=0решаем по отдельности каждое ур-ие 1) cosx-sinx=0   /:cosx≠01-tgx=0tgx=1x=pi/4+pik, k ∈Z 2) cosx+sinx= - 2√2(1/√2*cosx+1/√2*sinx)= - 2sin(pi/4)cosx+cos(pi/4)*sinx= -2/√2sin(pi/4+x)=-√2-√2=1,41нет реш. , т.к. x∈[-1;1] ОТВЕТ:pi/4+pik, k ∈Z